Aplikasi Augmented Reality Pengenalan Bangunan Adat Desa Penglipuran - Anak Agung Ngurah Hary Susila; Dewa Made Sri Arsa (STMIK Budi Darma, 2020)
Penglipuran Village is a tourism village on the island of Bali. One of the attractions of Penglipuran Village is the traditional, uniform building that has characteristics that are still maintained since ancient times. Many tourists who visit and take pictures in front of a traditional building, but do not know clear information about the name and function of the building. The purpose of this study is to design an application as an information medium for the introduction of traditional buildings in Penglipuran Village using Augmented Reality technology. The research model used for application design is the waterfall model. This Augmented Reality application was built with Autodesk Maya and Unity software so that it can display 3D custom building information to the real environment by using the brochure media as a marker. The results of the study were successful in designing an Augmented Reality application that can provide information about the traditional buildings of Penglipuran Village in the form of 3D animation, text and audio narration